Extensive Reading And Dictionaries An Approach To vocabulary acquisition To meet contextual requirements For Advanced English Language Learners - Fitri Rizki; Jalaluddin Jalaluddin (Universitas Lampung, 2018)
Fully understanding the message delivered in written English or Spoken English will save a lot of time for the readers as well as the lisnters to have the comprehension of the information conveyed..The use of appropriate words that represent what the writer or the speaker has in his mind has the potential to enable the readers or the listeners to take the required messages in the shortest possible time. With representivve vocabulary that are used to meet contextual requirements will guarantee a message to reach its required object. Correct use of words will create fully meaningful messages to their readers as well as listeners. By extensive reading and use of monolingual dictionaries, a learner will gain the vocabulary acquisition. DOI: http://dx.doi.org/10.23960/aksara/v19i2.pp114-126